The N‐terminal transactivation domain of the glucocorticoid receptor mediates apoptosis of human small cell lung cancer cells. Issue 12 (13th August 2014) - Singh, Nimisha; Taylor, Kerryn; Mjoli, Phiwokuhle B.; Poolman, Toryn; Ray, David W.; Sommer, Paula
<x xml:space="preserve">Abstract</x> Small cell lung cancer (SCLC) is an aggressive disease with a poor prognosis. These cancers are deficient in glucocorticoid receptor (GR) expression, and therefore, resistant to glucocorticoids. Overexpression of the GR both in vivo and in vitro leads to apoptotic cell death suggesting that loss of GR is favorable for cancer growth. Indeed, the GR promoter is silenced in SCLC cells by methylation. We now show that treatment of the SCLC cell line (DMS79) cells with the demethylating agent, 5‐aza‐2′‐deoxycytidine (5‐aza), results in significant endogenous re‐expression of both GRα and the ligand‐independent GR‐P. The GR gene has a complex promoter region comprising nine alternative promoters, the proximal seven of which lie within a CpG island. The endogenous re‐expression seen is attributed to the constitutive promoters 1B and 1C and 1J but predominantly 1F, which we show to be heavily methylated in SCLC cells. Flow cytometric analysis using the apoptotic marker, Annexin V, shows that this endogenous re‐expression is sufficient to drive the SCLC cells to apoptosis. Apoptotic induction is specific to GR re‐expression as cotreatment with 5‐aza and the GR antagonist, RU486 prevented apoptosis. Of the three functional GR domains (the DNA binding domain, ligand binding domain, and transactivation domain), we identified that the transactivation domain is essential for apoptosis in SCLC. The discovery that endogenous re‐expression of the GR in SCLC cells is sufficient to induce apoptotic cell death by reversing a cancer‐driven DNA methylation effect may lead to the development of novel adjunct therapies. © 2014 Wiley Periodicals, Inc.